A slot demand‐based path reservation approach for the timely and reliable delivery of bursty traffic in WMSNs. (3rd October 2014) - Vinh, Phan Van; Oh, Hoon; Xiang, Yang; Pathan, Mukaddim; Wei, Guiyi; Fortino, Giancarlo
Summary In case that we build a context‐aware computing‐based Safety Monitoring and Control System (SMOCS) that monitors the safety of the workers, many sensor devices with different data rates are distributed in the target field. Based on these context data, the SMOCS judges the safety of the working environment primarily. If it perceives a dangerous sign, it requests additional bursty data such as still image or video streaming from a particular sensor device in order to confirm the situation. Because these bursty data have to be delivered to the server reliably with time constraints, it is challengeable to process those data with limited energy and bandwidth. In this paper, we propose an efficient approach to deliver bursty data reliably by reserving time slots to transmit the required packets on all the paths from the selected multimedia nodes to the server. The nodes that are not on the selected paths are put into sleep mode to conserve energy during the transmission of bursty data. We evaluate the proposed approach by conducting experiments using the indoor test bed that consists of 30 sensor communication devices. The experimental results show that the proposed approach can satisfy the requirements of multimedia applications well. Copyright © 2014 John Wiley & Sons, Ltd.